Normative functional performance values in high school athletes: The functional pre-participation evaluation project - Onate, J. A.; Starkel, C.; Clifton, D. R.; Best, T. M.; Borchers, J.; Chaudhari, A.; Dawn Comstock, R. D.; Cortes, N.; Grooms, D. R.; Hertel, J.; Hewett, T. E.; Miller, M. M.; et al. (Journal of Athletic Training, 2018)
Context: The fourth edition of the Preparticipation Physical Evaluation recommends functional testing for the musculoskeletal portion of the examination; however, normative data across sex and grade level are limited. Establishing normative data can provide clinicians reference points with which to compare their patients, potentially aiding in the development of future injury-risk assessments and injury-mitigation programs.